Microsoft Power BI Cookbook Gain Expertise in Power BI with over 90 Hands-On Recipes, Tips, and Use Cases, 2nd Edition - Deckler, Greg (Packt Publishing, Limited, 2021)
Power BI is a business intelligence and analytics services tool by Microsoft designed to provide visual and interactive insights into data. This book will provide thorough, technical examples of using all primary Power BI tools and features as well as demonstrate high impact end-to-end solutions that leverage and integrate these technologies